Peranan Dana Perimbangan Terhadap Pertumbuhan dan Kesenjangan Ekonomi Daerah Kabupaten/Kota di Kalimantan Selatan - Dwi Putri Cesaria Aminellia; Muzdalifah Muzdalifah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study determines the role of balancing and profit-sharing funds for economic growth and a general allocation of funds for economic inequality. This study uses a scatter plot analysis of Klassen Typology in thirteen districts/cities in South Kalimantan from 2011-2019. The Klassen Typology here is divided into three years of observation. Two thousand eleven as a base year, 2015 as a middle year, and 2019 as a final year of observation. The observations are divided into balancing and profit-sharing funds for economic growth and general allocation funds for economic inequality. The secondary data used are from the Badan Pusat Statistik Kalimantan Selatan, which consists of data on the rate of economic growth and Gini Ratio, and from Direktorat Jenderal Perimbangan Keuangan used of balancing funds, profit sharing funds, and general allocation funds data.The Klassen Typology with the best results for balancing funds on economic growth is in quadrant II, with low balancing funds and high for economic growth. The regions that have improved economic growth are Banjar, Balangan, Kotabaru, Tanah Bumbu, Tanah Laut, and Tabalong; there are so many being in quadrant II, both in 2011-2019. The role of profit-sharing funds on economic growth is in quadrant I as the best result with high profit-sharing funds and high economic growth. Barito Kuala, Hulu Sungai Selatan, Hulu Sungai Tengah, and Hulu Sungai Utara have improved their economic growth over three years of comparison. The role of general allocation funds in economic inequality is in quadrant III for the best with high general allocation funds and low economic inequality. The regions with economic inequality decreased are Balangan, Barito Kuala, Tapin, Tanah Laut, Hulu Sungai Tengah, and Hulu Sungai Utara.